Description of High School Students' Career Adaptability - Eka Puteri Utami; Mamat Supriatna; Eka Sakti Yudha (Universitas PGRI Yogyakarta, 2024)
Career adaptive ability is able to express appropriate behavior in dealing with changing conditions. If individuals have high career adaptability skills, it will be easier for them to face challenges in achieving success. This study aims to describe the description of career adaptability. The method used in this research is quantitative, and the research design used is a survey. Respondents in this study were 325 students in class XI of a high school in Bangka Belitung Province. Collecting data in this study used a career adaptability instrument which was developed from various definitions of experts and has been previously validated. The career adaptability instrument consists of 60 statements and covers three aspects. It can be concluded that students' career adaptability skills are in the quite capable category with a percentage of 67.7%. This means that several aspects and dimensions of career adaptability are still lacking. Keywords: career adaptability, students, high school